Predictive and Prognostic Molecular Markers of Oral Cancers and Potential Therapeutic Agents Targeting These Markers - Shilpa Jain; Anil Goel; Arpita H Patel; Sarvatnida Shaikh (Indian Journal of Medical Biochemistry)
In the last two decades, there has been tremendous research in the field of oncogenesis at the molecular level. With the unveiling of various signaling pathways and molecular markers involved in oncogenesis, efforts are being made to develop therapeutic agents targeted at these molecular levels. Oral cancers constitute 40% of all head and neck cancers and are major health concerns all over the world. The age-adjusted incidence rate for oral cancer is 4 per 1,00,000 population in males and 2 per 1,00,000 population in females worldwide with an overall 5-year survival rate of 50–60%. About 30% of patients of oral cancer present with early-stage disease where surgery and/or radiotherapy can achieve cure rates of about 70–90%. However, the majority of patients present in locally advanced stages, where we have to use combined treatment modalities leading to more side effects and morbidity. The recurrence rate is also about 40–50% in advanced stages and there are limited treatment options available once the primary treatment modalities fail. Despite all the development in areas of genomics and proteomics of oncogenesis, there has not been a breakthrough in treatment modalities available or overall improvement in survival rates of such patients. This review intends to highlight the genomic alterations and signaling pathways involved in oral cancers. The biomarkers which can be used as predictive and prognostic markers in oral cancers which can be potential therapeutic targets will also be discussed in this review. The findings of available studies obtained from a literature search will be comprehensibly presented in this review.